2022
DOI: 10.1016/j.phyplu.2022.100233
|View full text |Cite
|
Sign up to set email alerts
|

In silico, in vitro screening of plant extracts for anti-SARS-CoV-2 activity and evaluation of their acute and sub-acute toxicity

Abstract: Background In the absence of a specific drug for COVID 19, treatment with plant extracts could be an option worthy of further investigation and has motivated to evaluate the safety and anti-SARS-CoV-2 activity of plant extracts. Purpose To screen the phytochemicals for anti-SARS-CoV-2 in silico and evaluate their safety and efficacy in vitro and in vivo. Method The phytoche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Therefore, phytochemicals derived from medicinal plants with activity against targets associated with SARS-CoV infection may provide valuable leads for drug development against novel SARS-CoV-2. Recently, studies have been conducted to develop SARS-CoV-2 3CLpro inhibitors from natural plants [33] . Some flavonoid derivatives, which are representative natural compounds, have an excellent effect on SARS-CoV-2 3CLpro [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, phytochemicals derived from medicinal plants with activity against targets associated with SARS-CoV infection may provide valuable leads for drug development against novel SARS-CoV-2. Recently, studies have been conducted to develop SARS-CoV-2 3CLpro inhibitors from natural plants [33] . Some flavonoid derivatives, which are representative natural compounds, have an excellent effect on SARS-CoV-2 3CLpro [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous organic solvents, without toxic effects on cells, are widely used for dissolving the hydrophobic compounds in different types of cell culture assays [79–81] . Therefore, in a preliminary assay, it is important to determine the maximum or minimum tolerable concentration for solvent on cell toxicity that can be used to prepare solutions of herbal extracts or other compounds [82–85] . Dimethyl sulfoxide (DMSO), ethanol and methanol are suitable solvents widely used as vehicles for drug delivery, [86] crude extraction, and dissolving various plant extracts for enhanced solubility in biological studies [87] .…”
Section: Methodsmentioning
confidence: 99%
“…This finding is supported by the results from Murugan et al's (2021) study, which suggested that neondrographolide is a compound with the potential as an inhibitor of RdRp even though its binding affinity value is greater than that of remdesivir drugs, which is due to the stability of its binding to the Asp336, Thr440, and Asp507 residues of the target protein. The study by Latha et al (2022) showed that andrographidin C, being one of the major diterpenoid compounds of A. paniculata, interacts with RdRp similarly to nucleotide analog drugs, that is, through non-obligate RNA chain breaks. Such interaction is stable due to the presence of pi-pi bonds from uracil bases and the affinity is also strengthened by hydrogen bonds at amino residues Glu811 and Lys551 (Dey et al, 2020).…”
Section: Rna-dependent Rna Polymerasementioning
confidence: 99%